Bringing Genome Tests into Clinical Practice - Sarkar, I.N. (Yearbook of Medical Informatics, 2013)
Objective: To provide a review of recent progress in the use of genomic data in clinical contexts.Method: Survey of key articles selected from the previous year (2012).Result: Two major themes emerged as areas of focus in 2012: (1) integration of genomic data into electronic health records; and (2) determining the clinical utility of genomic tests.Conclusion: Significant advances are being made towards the integration of genomic data such that they may useful for clinical decision making. While the short term advances will likely still be seen in clinically valid genotype-phenotype research, there have been promising advances towards developing genomic tests that may be of clinical utility in the near future.
Keywords: Translational Bioinformatics; Electronic Health Records; Genomics; IMIA Yearbook